Potential of modified rich-polyphenol red rice flour in production of healthy porridge for the elderly - Naphatrapi Luangsakul; Ngô Văn Tài (Journal of Agriculture and Food Research, 2025)
This study aimed to develop nutritionally enhanced red rice porridge suitable for elderly individuals by using native, ultrasonicated, and pregelatinized red rice flours (Hommali and Manpo). Porridges were formulated with 10 % and 15 % rice flour and evaluated for pasting and rheological properties, antioxidant release, and starch digestibility. All samples exhibited shear-thinning properties (n < 1). Ultrasonication, especially in the 15 % Manpo sample, significantly improved polyphenol release and reduced estimated glycemic index (eGI = 63.25), while achieving spoon-thick texture (IDDSI Level 4). Pregelatinized flours showed rapid rehydration, suitable for instant product. A high eGI (73.96) was also observed in the sample utilizing Hommali pregelatinized rice flour at a concentration of 10 %. Multivariate analysis confirmed the influence of flour modification and amylose content on functional attributes. These findings support ultrasound as a promising green technology for elderly-targeted porridge products. Especially, ultrasonicated red rice flour, particularly at 15 % concentration, provided an optimal balance between texture and functional bioactivity, making it a promising ingredient for elderly-focused nutritional products. • Ultrasound-treated red rice improved porridge texture and reduced glycemic index. • Modified Manpo rice flour at 15 % gave optimal IDDSI Level 4 consistency. • Ultrasonication enhanced polyphenol release and antioxidant activity in porridge. • Pregelatinized flour ensured instant rehydration and smooth porridge formation. • PCA and HCA confirmed modification effects on porridge texture and digestibility.
Keywords: Food composition and properties; Food and Agricultural Sciences; Microbial Metabolites in Food Biotechnology